MYSTICISM IN BATIK INDUSTRIAL RELATION: The Study of Trust Achievement on the Survivability of Small-Medium Batik Industry at Pekalongan City (JOURNAL OF INDONESIAN ISLAM, 2012)
Relationship between economy and religion had been known for long time ago as it was found in Max Weber’s books “The Protestant Ethic and The Spirit of Capitalism” and “The Protestant Sects and The Spirit of Capitalism”. This paper examines the extent to which mysticism practices have been conducted among the employers and employees of Batik Industries in Pekalongan City. It argues that mysticism has an important role to reinforce the social capital and make the industry survive, especially to face many problems related to productivity, motivation, trust as well as wage issues. By practicing mystics and religious traditions, like dhikiran, manakiban, hawl and muludan, people have spiritual force which has an important role both for personally and professionally in the work place, especially to maintain the relationship between employees and employers. Also they could be stronger when faced the changes and challenges of business and their industry can survive.